Residual wage inequality in urban China, 1995 - 2007 - Chunbing Xing (Institute for the Study of Labor (IZA), 2010)
We use three waves of urban household survey data from 1995 to 2007 to investigate the trends of residual inequality and its determinants. First, we describe the change of overall and residual wage inequality over time. One important new pattern is that the rise in both the overall and residual inequality mainly happened at the upper half of the wage distributions (i.e. the rich are getting relatively much richer) from 2002 to 2007. From 1995 to 2002, however, it is truer to say that the poor are getting relatively much poorer. Second, by using two complementary semi-parametric methods, we find that the composition effect is negligible. Instead, the change in skill prices plays a dominant role in the rise of residual inequality. Finally, by constructing a panel data at the city level, we find that ownership restructuring is an important factor that has caused the skill price to rise, especially in the earlier period. Another finding is that China's export share of GDP has a positive effect on the enlargement of the upper half distributions. This effect is more significant in the latter period from 2002 to 2007, highlighting the impact of China's entry into the WTO.
Keywords: J3; 330; Urban China; residual inequality; decomposition; Lohnstruktur; Qualifikation; Soziale Ungleichheit; Städtischer Arbeitsmarkt; China